Plasma Estradiol Profile After Administration of Different Types of Estradiol Esters in Acyclic Mares - Setoguchi, Leticia S.; Siqueira, Leonardo M.; Lucca, Leticia K.; Oquendo, Pedro S.; Oquendo, Fabiana M.G.; Nogueira, Guilherme P. [UNESP]; Silva, Elisa S.M. (Elsevier, 2023)
Although the use of different estradiol esters has been extensively studied in hormonal protocols in cows, such information is lacking in mares. The present study aimed to assess the effects of treatment with the same doses and administration frequency of estradiol cypionate, estradiol benzoate and 17β estradiol on plasma estradiol (E2) concentrations of acyclic mares and correlate the E2 profile to the endometrial edema score. Sixteen treatments were performed in 14 mares randomly divided into three groups: EB (n = 5), EC (n = 5), and 17β (n = 6), receiving 10 mg on day 0 (D0), 6 mg on D1, and 4 mg on D2 of estradiol benzoate, estradiol cypionate, and estradiol 17β, respectively. Blood samples, rectal palpations, and ultrasound evaluations were performed once daily, starting before the first estradiol treatment (D0) until edema disappearance or D8. Moderate to high edema was observed in all groups 24 hours after the first estradiol administration. Edema persisted above score 2 until D7, D5, and D4 in groups EC, EB, and 17β, respectively. Higher edema was found on D2 in EB group compared to 17β, on D6 and D7 in EC compared to 17β, and on D8 in EC compared to EB (p ≤ .05). Maximum E2 concentrations were detected on D1 in groups: EB, showing a sharp decrease from D2 to D3 (p < .0001); and 17β, where no differences were observed between treatment days (p ≥ .05). In the EC group, maximum concentrations were observed on D2, which remained high from D2 to D4 compared to the other days (p < .0001). Plasma concentration of E2 was higher in EB than the other groups on D0 and D1, and EB>EC>17β on D2. Plasma E2 concentrations and edema score were positively correlated, being moderate in groups EB and EC and weak in the 17β group. In conclusion, the most pronounced plasma E2 concentration was observed in EB group 24 hours after the administration of the first dose. Estradiol concentrations peaked 48 hours after EC administration, while a distinct peak was not observed in a 24h interval evaluation in the 17β group. Moreover, high edema does not necessarily reflect on high E2 concentrations in acyclic mares.
Keywords: Acyclic mares; Estradiol esters; Estrogen; Plasma profile